CE analysis of single wood cells performing hydrolysis and preconcentration in open microchannels. Issue 2 (9th December 2013) - Rokhas, Maria Khihon; Mikkonen, Saara; Beyer, Juliane; Jacksén, Johan; Emmer, Åsa; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> In the present work, monosaccharides from pulp samples and single wood fibers were analyzed with CE, using indirect detection due to the lack of chromophores on the monosaccharides. The hydrolysis degradation of cellulose and hemicellulose into monosaccharides was performed using TFA, either in bulk scale or in microscale. In the microscale, one single wood fiber was hydrolyzed in an open microchannel manufactured on a silicon microchip with the dimensions 50 μm × 50 μm (length 1 or 3 cm). The low monosaccharide amounts derived from a single fiber implied that a preconcentration step was necessary to increase the detectability. Thus, an electromigration preconcentration of the hydrolyzed samples was performed within the microchannel, which resulted in a significantly enhanced signal intensity of the monosaccharides. In addition to the experimental study, computer simulations were performed regarding the preconcentration step of monosaccharides. The results from these simulations correlated well with the experimental results.